Gully Development Mapping for Effective Remediation and Control Using Geospatial Technology - Charles Udosen; Okon Efiong Ubom; Abasi-Ifreke S. Etok (Challenging Issues on Environment and Earth Science Vol. 4, 2021)
In south-eastern Nigeria, gully erosion has assumed an alarming proportion and this prompted the use of geospatial information technology to map a gully erosion site in Oron, Akwa Ibom State for effective remediation and control. Ground controls were provided in the vicinity of the gully head through the use of dual frequency Leica GPS 1200. The initiation and growth of gullies, releases large amounts of sediments into receiving streams thereby polluting sources of water supply to the rapidly increasing urban population. The obtained data were downloaded and processed using Leica Geo Office 8.3 and the processed data exported to Arc GIS 10.1 and Auto CAD Civil 3D 2013 for terrain analysis-DEM, Also, the Leica Total Station TS 06 was employed to carry out topographic mapping. The delineated runoff contributing area aided in the computation of maximum discharge (using the Rational method). The computed runoff of 33.919m3/s accounts for the rapid rate gully headscarp retreat at the rate of 1.2 m/day during the month of July, prior to intervention by the state government. The results obtained were employed in designing gully control structures.